ANALYSIS OF MATHEMATICAL COMPETENCE AMONG STUDENTS OF TRANSCARPATHIAN SCHOOLS - CSERNICSKÓ, ISTVÁN; KUCHINKA, KATALIN; DOROVTSI, ADAM (Herald of Khmelnytskyi National University. Technical sciences, 2025)
The assessment of students’ academic performance in relation to various socio-demographic factors remains a central focus in contemporary educational research. Mathematical competence occupies a particularly significant role among school subjects, as it reflects students’ mastery of curricular content and foundational knowledge. It also serves as a key indicator of cognitive development, logical reasoning skills, analytical thinking, and preparedness for participation in a knowledge-based, technologically advanced society. Consequently, mathematics performance is frequently used as a benchmark for evaluating educational quality at both national and international levels. International large-scale assessments, such as the Programme for International Student Assessment (PISA), extend beyond subject-specific evaluations by highlighting the broader educational context, including issues of equity, access to resources, socio-economic conditions, and cultural background. Findings from such studies consistently demonstrate that variables such as parental education level, student gender, and family socio-economic status have a substantial impact on academic outcomes. At the same time, while international studies provide valuable comparative insights, they do not always capture the regional specificities of educational systems. Therefore, local or regional assessments are essential for better understanding the particular challenges and opportunities within local education systems. Such assessments help identify problem areas and support the development of effective education policies. This study presents the findings of a regional mathematics competence assessment conducted in 2024 among 6th and 8th grade students in schools in Transcarpathia, where the teaching is conducted in Hungarian. The main objective of the research is to evaluate the impact of gender, parental education level, and multilingualism on students’ mathematical performance.